Shallow water regime in the Chambal command area, western India: environmental implications of modification in surface drainage (Journal of Nepal Geological Society, 1998)
Introduction of canal irrigation in the Kota region (western India) has significantly modified the groundwater regime of the region and has resulted in water logging and soil salinisation. Present paper focuses on diagnosis and correlation of such problems with surface irrigation in the Left Main Canal region of the Chambal command area. The results of the studies carried out for a two year period (1994- 1996) have been discussed.The area of present investigation is predominantly alluvial covered with limestone-sandstone ridges, belonging to the Vindhyan Supergroup (late Proterozoic), exposed along the western and southwestern fringe. The water table is controlled by the topography and both the pre- and post-monsoon water table profiles are quite similar. The seasonal water table fluctuation varies from 1.62 to 8.82 m. Major part of the area of study having water level depth < 6 m falls under the category of shallow water table zone. The region with